2013
DOI: 10.1007/s00414-013-0850-7
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls at the root of facial assessment on photographs: a quantitative study of accuracy in positioning facial landmarks

Abstract: In the last years, facial analysis has gained great interest also for forensic anthropology. The application of facial landmarks may bring about relevant advantages for the analysis of 2D images by measuring distances and extracting quantitative indices. However, this is a complex task which depends upon the variability in positioning facial landmarks. In addition, literature provides only general indications concerning the reliability in positioning facial landmarks on photographic material, and no study is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 12 publications
3
39
4
2
Order By: Relevance
“…The availability of child pornographic images has grown exponentially with the development of the internet resulting in millions of images of CSA, which are shared and downloaded online (4,7,8). Consequently, there has been a rise in the number of cases in which an expert has been called upon to give an age assessment from a photograph of alleged CSA (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The availability of child pornographic images has grown exponentially with the development of the internet resulting in millions of images of CSA, which are shared and downloaded online (4,7,8). Consequently, there has been a rise in the number of cases in which an expert has been called upon to give an age assessment from a photograph of alleged CSA (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Visual assessment of age from pornographic images has been based on the evaluation of the Tanner stages of development and other sexual maturity indicators, with the face also suggested to be an important feature for analysis (8,12). However, studies have shown that age estimation from secondary sexual characteristics is inaccurate, with wide variability in the choice of features believed to be most important in age assessment (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite some authors considering this technique as a valid identification method [6], [8], [9], [20], many others only regard CFS as a tool for the exclusion method [21]- [23]. The fact that two different objects have to be compared implies a number of sources of uncertainty, making CFS identification a subjective technique, highly dependent on the forensic anthropologist's experience and knowledge: acquisition parameters of the photographs [24], [25], mandible articulation, landmark location imprecision [26], soft tissue depth variability [15], and ultimately morphological comparison.…”
Section: Introductionmentioning
confidence: 99%